In Vivo Reconstitution of the FhuA Transport Protein of Escherichia coli K-12 - Braun, Michael (American Society for Microbiology, 2003)
The FhuA protein in the outer membrane of Escherichia coli actively transports ferrichrome and the antibiotics albomycin and rifamycin CGP 4832 and serves as a receptor for the phages T1, T5, and φ80 and for colicin M and microcin J25. The crystal structure reveals a β-barrel with a globular domain, the cork, which closes the channel formed by the barrel. Genetic deletion of the cork resulted in a β-barrel that displays no FhuA activity. A functional FhuA was obtained by cosynthesis of separately encoded cork and the β-barrel domain, each endowed with a signal sequence, which showed that complementation occurs after secretion of the fragments across the cytoplasmic membrane. Inactive complete mutant FhuA and an FhuA fragment containing 357 N-proximal amino acid residues complemented the separately synthesized wild-type β-barrel to form an active FhuA. Previous claims that the β-barrel is functional as transporter and receptor resulted from complementation by inactive complete FhuA and the 357-residue fragment. No complementation was observed between the wild-type cork and complete but inactive FhuA carrying cork mutations that excluded the exchange of cork domains. The data indicate that active FhuA is reconstituted extracytoplasmically by insertion of separately synthesized cork or cork from complete FhuA into the β-barrel, and they suggest that in wild-type FhuA the β-barrel is formed prior to the insertion of the cork.